(untitled) (Revista Espinhaço, 2018)
Based on historiographic approach, this paper discusses the representations of the spacial organization of the province of Minas Gerais (nineteenth century), existents in works of political, economic and demographic history. Stands out the formation and the characteristic features of the spatial metaphor “Minas mosaic”, as well as the reasons for its long validity in the Minas Gerais historiography. In sequence, the idea of the “Minas mosaic” is criticized and the necessity of formulate of new representation of the provincial space is affirmed, based in the results of recent researches in Economic History, highlighting the contact, the interaction and the differentiation between the regional sub-spaces.